Country Partnership Framework for the Republic of Cameroon for the Period FY17-FY21 - World Bank Group (World Bank, Washington, DC, 2017)
This Country Partnership Framework (CPF) covers the period FY17-FY21. It sets outthe World Bank Group’s (WBG) proposals for supporting the Government of Cameroon’s (GoC) objectives for inclusive growth and poverty reduction, its commitment to the SustainableDevelopment Goals (SDGs) and its responsibilities and priorities in the area of climate changemitigation and adaptation. The GoC’s long-term vision, ‘Cameroon Vision 2035’, is of ‘an emerging, democratic and united country in diversity’. To operationalize this Vision, the Government adopted a Growth and Employment Strategy (‘DSCE’, ‘Document de Stratégie pour la Croissance et l’Emploi’) in 2009 and defined specific objectives to be achieved by 2020. The GoC has further adopted the United Nations 2030 Agenda for Sustainable Development. It also endorsed the Paris Agreement under the United Nations Framework Convention on Climate Change and published Cameroon’s Nationally Determined Contributions (NDC) setting out its contribution to climate change mitigation and priorities for adaptation. The CPF draws on a comprehensive Systematic Country Diagnostic (SCD, report 103098-CM), completed duringFY16, which identified constraints to achieving the World Bank’s Twin Goals of eliminatingpoverty and fostering shared prosperity in a socially and environmentally sustainable way. TheCPF also benefited from other pieces of analytical work, including a gender assessment and afragility assessment carried out in 2015. Cameroon’s vision of becoming an upper middle-income country, and of reducing poverty to less than 10 percent by 2035 (29 percent by 2020), is highly ambitious. It would simply an annual real GDP growth of 5.5 percent per capita during the period, which would represent a marked increase from historical patterns, and strong sector, social and spatial policies that can reverse the inequalities observed over the past two decades. The SCD points to three main areas of constraints - and opportunities - to achieving these objectives: (i) low rural productivity, particularly in northern regions; (ii) a non-conducive business environment for the formal and informal private sector; and (iii) fragility and poor governance of the private and public sectors.